The effect of fish oil capsule on serum total cholesterol and triglycride levels in type-2 diabetic patient - Habib, Tamanna Binte; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2018)
Background: Diabetes Mellitus (DM) is one of the common metabolic disorders that have effects on lipid metabolism. Fish oil supplementation may improve lipid abnormalities in diabetic patient.Objective: To observe the effect of supplementation of omega-3 fatty acid on total cholesterol (TC) and triglyceride(TG) level in type 2 DM. Methods: A prospective interventional study was conducted from January 2017 to December 2017. A total numbers of 52 diagnosed type 2 diabetic patients of both sexes were selected with age 40 to 50 years. Among them, 27 type 2 diabetic patient with supplementation of omega 3 fatty acid (2g/ day) for 12 weeks was considered as study group. Another 25 type 2 diabetic patients without supplementation of omega 3 fatty acid was considered as control group. The study subjects were selected from Outpatient Department of Endocrinology, Dhaka Medical College Hospital, Dhaka and personal contact from Dhaka city.Serum TC and TG were estimated by enzymatic endpoint method in autoanalyzer. The study parameters were measured at base line and after 12 weeks of study period in both groups. For statistical analysis, Paired Student’s‘t’ test and Unpaired Student’s ‘t’ test were performed as applicable using SPSS for windows version 16.0. Results: In this study serumTC and TG levels were significantly lower (p<.001) in diabetic patients after supplementation with omega- 3 fatty acid in comparison to that of their baseline value.Again, after 12 weeks, serum TC and TG levels were significantly lower (p<.001) in diabetic patients after supplementation with omega-3 fatty acid in comparison to control group. In control group, serum TC and TG levels were almost similar both at baseline and after 3 months of follow-up. Conclusion: After analyzing the results of the study, it can be concluded that omega-3 fatty acid may improve serum TC and TG levels in type 2 diabetic patient and may be helpful to minimize the complications of type-2 DM. J Bangladesh Soc Physiol. 2018, December; 13(2): 73-77